Dopaminergic system and its relationship with the hypothalamic-pituitary-gonadal and hypothalamic-pituitary-thyroid systems (review) - I. N. Molodovskaya (Сибирский научный медицинский журнал, 2020)
This article reviews literature data on the activity of the central and peripheral dopaminergic systems, as well as its relationship with the hypothalamic-pituitary-gonadal and hypothalamic-pituitary-thyroid systems. Studies have shown that dopamine levels vary depending on the territory of residence, while the data on the age dynamics of the plasma dopamine level contradict each other, which does not allow an unambiguous conclusion about a decrease or increase in its level with age. Most studies focus on the functions of dopamine in the central nervous system. Symptoms of several brain diseases, including schizophrenia, Parkinson’s disease, attention deficit and hyperactivity disorders and depression, are alleviated by the pharmacological modulation of dopamine transmission. However, there is evidence of a functional role of peripheral dopamine. While dopamine of the central dopaminergic system inhibits the secretion of thyrotropin, dopamine synthesized by sympathoadrenal nerve cells, heparinocytes, and thyroid parafollicular cells on the periphery stimulates the formation and release of iodothyronines. The neuroprotective effects of sex steroids determine the prevalence of studies of their role in preservation and maintaining the activity of the dopaminergic system. The dopaminergic system also affects the levels of sex hormones, enhancing aromatase activity, inhibiting the synthesis or secretion of prolactin, regulating the levels of gonadotropins and steroidogenesis in Leydig cells. The peripheral and central dopamine systems are sensitive to environmental influences, which indicate the relationship between the peripheral and central links.